Les Nouveaux Europeens 1982. (Paris : Galerie Eric Fabre, 1982)
Rösel, Karel ; Lavier, Bertrand ; Woodrow, Bill ; Présence Paunchounette ; Gherban, Alexandre ; Sytour, Patrick
Les Nouveaux Europeens 1982, Galerie Eric Fabre, Paris, Mai 1982
boek